14 Orthopaedic Post-Operative Elective Proforma. (4th May 2021) - Castelhano, R; Kakkar, V
Abstract: Introduction: Post-operative daily reviews are essential for a safer post-op recovery and must recognise, early, potential complications and prevent their advance. The fast turnover of Junior Doctors and often T&O being their first surgical rotation, leads to a decrease in knowledge of which aspects are important to assess in a post-op patient. The aim of this project was to create a proforma that helps in assessing elective post-op patients and reduce mistakes. Method: QI methodology was applied and a proforma was created and made available in every set of notes of elective patients. Awareness was raised about the proforma which was done at the time of the induction of the new doctors which corresponded to separate PDSA cycles. Results: Following cycle 1, the adhesion was 98%. VTEP, analgesia, Xray reviewed, examinations were documented in 100% of the patients. The PDSA cycle 2 coincided with the new incoming doctors, despite the efforts, there was poor compliance. The notes were reviewed: VTEP, analgesia and examination were not documented, post-op x-rays were reviewed in 60%. Conclusions: The PDSA cycle 2 showed how the proforma increases patient safety with good documentation and should continue to be used by the Department.